2007
DOI: 10.1074/jbc.r600026200
|View full text |Cite
|
Sign up to set email alerts
|

Classical Nuclear Localization Signals: Definition, Function, and Interaction with Importin α

Abstract: The best understood system for the transport of macromolecules between the cytoplasm and the nucleus is the classical nuclear import pathway. In this pathway, a protein containing a classical basic nuclear localization signal (NLS) is imported by a heterodimeric import receptor consisting of the ␤-karyopherin importin ␤, which mediates interactions with the nuclear pore complex, and the adaptor protein importin ␣, which directly binds the classical NLS. Here we review recent studies that have advanced our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
988
4
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,018 publications
(1,012 citation statements)
references
References 62 publications
13
988
4
7
Order By: Relevance
“…We further demonstrate that phosphorylation at the Ser141 residue, the N-terminal region (aa 1-43) and the putative NLS region (aa 143-159) are crucial for nuclear translocation of SIP. These data are consistent with the contention that the nuclear import of most signaling proteins is NLS-dependent and is regulated by protein modifications, such as phosphorylation (Jans and Hubner, 1996;Lange et al, 2007). Interestingly, although curcumin-resistant subline MOLT-4/AraG shows defect in both SIP phosphorylation and nuclear translocation, it contains an SIP-WT sequence identical to that in MOLT-4, according to our direct sequencing data (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We further demonstrate that phosphorylation at the Ser141 residue, the N-terminal region (aa 1-43) and the putative NLS region (aa 143-159) are crucial for nuclear translocation of SIP. These data are consistent with the contention that the nuclear import of most signaling proteins is NLS-dependent and is regulated by protein modifications, such as phosphorylation (Jans and Hubner, 1996;Lange et al, 2007). Interestingly, although curcumin-resistant subline MOLT-4/AraG shows defect in both SIP phosphorylation and nuclear translocation, it contains an SIP-WT sequence identical to that in MOLT-4, according to our direct sequencing data (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…As we know, small proteins (MW o40 kDa) may, in principle, diffuse passively through the nuclear pores (Lange et al, 2007). However, it has been shown that SIP can self-dimerize through the N-terminal aa 1-47 (Santelli et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal domain contributes at least three of the four non-contiguous, positively charged determinants that we propose conform the AID NLS. Binding to importin-α adaptors, which mediate the nuclear import of proteins with classical basic NLS 29,30,36 , is in line with this. Without the 3D structure of an AID-importin complex it is difficult to assign which residues make direct contact and which play a structural role in displaying those residues.…”
Section: Active Nuclear Import Of Aidsupporting
confidence: 59%
“…4 b). This kind of NLS is recognized by members of the importin-α family of adaptors 29,36 . Indeed, AID-Flag was pulled down from extracts of Ramos cells by GST-importins-α1, α3 and α5 (Fig.…”
Section: Aid Has a Conformational Positively Charged Nlsmentioning
confidence: 99%
“…Classical NLSs (cNLS) can bind to importin α through either a major site, a minor site, or both 8, 9. Monopartite cNLSs consist of a single cluster of positively charged residues, primarily lysines or arginines, that assume an ordered state once bound to importin α 10…”
mentioning
confidence: 99%